Sea mysteries - Smith, Siân (Legends of the sea., 2010)
Mysteries of the sea have enchanted and perplexed people for centuries. Through simple text and photographs, this book introduces readers to the famous sea tales of the Bermuda Triangle, mermaids, ghost ships, and Atlantis, and encourages them to think critically to deduce whether the legends are true.